Spontaneous enterocutaneous fistula in a neonate: A case report - Yirgalem Teklebirhan Gebreziher; Yoseph Equar Assefa; Hadush Tesfay Negash; Fekrey berhe Gebru (Elsevier, 2025)
Introduction: Spontaneous enterocutaneous fistulas (ECF) are extremely rare in children. To our knowledge, only two cases have been reported in the literature. Case presentation: A male born vaginally at 34 weeks of gestation was referred to our hospital at 11 days of life due to a 4-day history of feculent discharge from a right upper quadrant wound. His birth weight was 1.6 kg, and his Apgar scores were 8 and 9 at 1 and 5 minutes, respectively. He had a black blister in the right upper quadrant of the abdomen at birth, which started to ulcerate and increase in size in the following days. He was initially treated with intravenous antibiotics and wound care. On day of life 7, the wound began discharging feculent material. On arrival, his vital signs were within normal limits. A 4 × 4 cm ulcerated wound was noted in the right upper quadrant of the abdomen, with two separate fistula sites, consistent with ECF. The rest of the examination was unremarkable. Abdominal X-ray was normal. The patient was taken to the operating room for an abdominal exploration, which was done through a supraumbilical transverse laparotomy separate from the area of the ECF. We found a 0.5 × 0.5 cm perforation on the hepatic flexure of the colon and a large perforation in the ileum, 40 cm proximal to the ileocecal valve. The colonic perforation was primarily repaired, the perforated ileal segment was resected, and the intestinal continuity restored with an end-to-end anastomosis. The postoperative recovery was uneventful, and he was discharged on the sixth postoperative day. Histopathological examination of the resected bowel revealed normal bowel mucosa, with no evidence of ectopic gastric or pancreatic tissue. Conclusion: Spontaneous ECF is an uncommon occurrence in neonates and children. Early surgical intervention is an effective management approach.